Assessing effective population size, coancestry and inbreeding effects on litter size using the pedigree and SNP data in closed lines of the Iberian pig breed. (8th June 2015) - Silió, L.; Barragán, C.; Fernández, A.I.; García‐Casco, J.; Rodríguez, M.C.
Summary: The complete pedigree of two closed Iberian pig lines ( Gamito and Torbiscal ), with 798 and 4077 reproducers, has been used to measure the evolution of coancestry ( f ) and inbreeding ( F ) for autosomal and X‐linked genes along 16 and 28 respective equivalent discrete generations. At the last generation, the mean values of each line were f  =   0.41 and 0.22, F  =   0.35 and 0.18, f X  = 0.46 and 0.22 and F X  = 0.47 and 0.19, respectively. Other calculated parameters were the effective number of founders (final values, 6.8 and 35.2) and non‐founders (1.5 and 2.4), founder genome equivalents (1.2 and 2.3) and effective population size (16.0 and 57.7). Measures of Torbiscal effective size based on rates of coancestry (66.1), inbreeding (65.0) and linkage disequilibrium (71.0) were estimated from whole‐genome SNP genotyping data. Values of new and old inbreeding and their respective rates by generation were computed to detect purging effects of natural selection. The analysis of 6854 Torbiscal litters showed significant negative impacts of new and fast inbreeding on litter size, as expected from the purging hypothesis: −0.20 born piglets per litter by a 10% of new inbreeding, and −0.03 and −0.02 piglets by 1% of total and new inbreeding rates, respectively. The analysis performed on 1274 litters of the Gamito line failed to show purging effects. The only significant results were reductions in −0.91 and −0.17 piglets by a 10% of old and X‐linked genes inbreeding, respectively. These results may be useful for some practical issues in conservation programs of farm or captive wild animals.